In discordance with the Scriptures : American Protestant battles over translating the Bible - Thuesen, Peter Johannes, 1971- (Religion in America series., 1999)
The story of the translation of the Bible in America begins with the King James Version. In fact, many Americans thought of the KJV as the foundational text of the Republic, rather than a cultural inheritance from Anglican Britain. In the nineteenth century, however, as new editions of the Greek New Testament appeared, scholars increasingly recognized significant errors and inconsistencies in the KJV. This soon led to the Bible revision movement, whose goal was the uniting of all English-speaking Protestants behind one new, improved version of the Bible. Ironically, as Peter Thuesen shows in this fascinating history, the revision movement in fact resulted in a vast proliferation of English scripture editions and an enduring polarization of American Christians over versions of holy writ. This proliferation of translations, he argues, shows something important about contemporary attitudes toward scripture. Although the Bible is regarded as immutable, conservatives and liberals alike now believe the text must evolve to fit the needs of each era.